1970
DOI: 10.1042/bj1160797
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification and properties of an enzyme from rat liver that catalyses the sulphation of l-tyrosyl derivatives

Abstract: 1. An enzyme that catalyses the transfer of sulphate from adenosine 3'-phosphate 5'[(35)S]-sulphatophosphate to l-tyrosine methyl ester and tyramine was purified approx. 70-fold from female rat livers. 2. The partially purified preparation is still contaminated with adenosine 3'-phosphate 5'-sulphatophosphate-phenol sulphotransferase (EC 2.8.2.1), but a partial separation of the two enzymes can be achieved by chromatography on columns of Sephadex G-200 and DEAE-Sephadex. 3. The enzyme responsible for the sulph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1970
1970
2000
2000

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…On enzymic hydrolysis, using either limpet arylsulphatase B or mylase (Koch Light), it was again totally hydrolysed liberating tyramine. Authentic tyramine-O-sulphate (Mattock & Jones, 1970) Klipstein (1964) reported that the highest incidence of subnormal serum folate concentrations occurred in epileptic patients who had been treated with phenytoin for long periods, but found no correlation between drug dose and the concentration of serum folate. The present experiment investigates the effect on concentrations of folate in serum and red cells of a short course of phenytoin in normal subjects.…”
Section: Clinical Pharmacology Sectionmentioning
confidence: 99%
“…On enzymic hydrolysis, using either limpet arylsulphatase B or mylase (Koch Light), it was again totally hydrolysed liberating tyramine. Authentic tyramine-O-sulphate (Mattock & Jones, 1970) Klipstein (1964) reported that the highest incidence of subnormal serum folate concentrations occurred in epileptic patients who had been treated with phenytoin for long periods, but found no correlation between drug dose and the concentration of serum folate. The present experiment investigates the effect on concentrations of folate in serum and red cells of a short course of phenytoin in normal subjects.…”
Section: Clinical Pharmacology Sectionmentioning
confidence: 99%
“…Although sulphate conjugates of phenol were first isolated and identified in mammals im the latter part ofthe last century, the mechanism ofthis reaction was not fully established until the discovery ofthe enzymic activation of sulphate and the isolation and identification of active sulphate, 3'-phosphoadenylyl sulphate (adenosine 3'-phosphate 5'-sulphatophosphate) some 15-20 years ago (Bernstein & McGilvery, 1952;DeMeio et al, 1953;Segal, 1955;DeMeio et al, 1955;Hilz & Lipmann, 1955;Robbins & Lipmann, 1956a,b, 1957. Studies on sulphate transfer from 3'phosphoadenylyl sulphate to various acceptors including mammalian hormonal steroids and L-tyrosine methyl ester have been actively pursued in the last few years. In mammals much of the recent emphasis on sulphoconjugation has been centred around the purification and characterization of the individual enzymes within the complex-forming family of sulphotransferases (Nose & Lipmann, 1958;Banerjee & Roy, 1966, 1968Hidaka et al, 1969;Mattock & Jones, 1970;McEvoy & Carroll, 1971). It now appears that in mammalian tissues there are at least four different sulphotransferases (Dodgson & Rose, 1970;Roy, 1970), which according to acceptor specificity are designated as phenol sulphotransferase (3'-phosphoadenylyl sulphate-phenol sulphotransferase, EC 2.8.2.1), 3fl-hydroxy steroid sulphotransferase (3'phosphoadenylyl sulphate-3p-hydroxy steroid sulphotransferase, EC 2.8.2.2), oestrone sulphotransferase (3'-phosphoadenylyl sulphate-oestrone sulphotransferase, EC 2.8.2.4) and L-tyrosine methyl ester sulphotransferase.…”
mentioning
confidence: 99%
“…This enzyme required added thiol for full activity and showed no requirement for magnesium ions. Mattock & Jones (1970) purified from female rat livers an enzyme that catalysed the sulphurylation of L-tyrosine methyl ester but this 70-fold purified preparation was contaminated with phenol sulphotransferase. The enzyme from rabbit liver which catalysed the sulphurylation of 5-hydroxytryptamine was purified 67-fold and this partially purified enzyme also catalysed the synthesis of p-nitrophenol sulphate (Hidaka, Nagatsu & Yagi, 1969).…”
mentioning
confidence: 99%